2013
DOI: 10.5406/bulcouresmusedu.195.0041
|View full text |Cite
|
Sign up to set email alerts
|

Trading Hindemith for "Hugs, High-fives, and Handshakes": One Preservice Music Teacher’s Decision to Teach Elementary General Music

Abstract: Existing research suggests that the high school ensemble experience is often a strong influence in the decision to teach music and that the majority of music education students plan to teach in a secondary ensemble setting. The purpose of this instrumental case study was to explore the experiences and beliefs of one male undergraduate music education student who chose a student-teaching placement (and subsequent career) in an elementary general music setting rather than his original intent to become a band dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 24 publications
3
21
1
Order By: Relevance
“…This connects with the broadened definition of school music that Nicole began to instill in her students and in her community, similar to beliefs held by other elementary general music teachers (Shouldice, 2013) and by music teachers using informal learning approaches (Abramo & Austin, 2014; Kastner, 2012). Nicole had a reconceptualized view of repertoire.…”
Section: Discussionsupporting
confidence: 59%
“…This connects with the broadened definition of school music that Nicole began to instill in her students and in her community, similar to beliefs held by other elementary general music teachers (Shouldice, 2013) and by music teachers using informal learning approaches (Abramo & Austin, 2014; Kastner, 2012). Nicole had a reconceptualized view of repertoire.…”
Section: Discussionsupporting
confidence: 59%
“…It is notable that most of the participants in this study did not seem to have a strong band director identity. This was also the case for Shouldice’s (2013) participant, who identified as a “teacher” rather than a “director.” Future research might investigate how one’s degree of “ensemble director identity” relates to their ultimate career choice as well as to their perceptions of the “status quo” in secondary instrumental music. Are those who do have a strong band director identity less likely to perceive a problem with the status quo?…”
Section: Discussionmentioning
confidence: 85%
“…While the aforementioned studies shed light on experiences of male EGM teachers, the researchers did not specifically examine why male instrumentalists choose to teach EGM or how their reasons might differ from those of female instrumentalists. In a case study of one male preservice teacher, Shouldice (2013) found that work-life balance was not a factor in his decision but that his dissatisfaction with band culture and his desire to be student centered were strong influences. Undergraduate coursework helped him realize that EGM teaching “was much more complex and fulfilling than [he] had previously thought” (p. 47).…”
mentioning
confidence: 99%
“…However, Tony’s (Roulston & Mills, 2000) accounts of “hen parties” are almost identical to Mike’s accounts of one of his workplaces, even to the specific analogy. Similar to Pete (see Shouldice, 2013), all participants reported that they wanted to teach at the elementary level and that it was not a means to a secondary position.…”
Section: Discussionmentioning
confidence: 73%
“…Brian left elementary school teaching to pursue a middle school chorus position partly because of these perceived suspicions. More recently, in an instrumental case study, Shouldice (2013) studied one male undergraduate’s choice to become an elementary general music teacher. For Pete, critical experiences in his coursework and dissatisfaction with band culture were among the factors that led to his career shift.…”
Section: Introductionmentioning
confidence: 99%